The Impacts of Urbanization on Carbon Emission Performance: New Evidence from the Yangtze River Delta Urban Agglomeration, China - Wenyi Qiao; Yike Xie; Jun Liu; Xianjin Huang (Land)
Regarding the carbon emission performance of urbanization, the changes in carbon emissions and carbon sinks have attracted particular attention, while the internal impact mechanism has been under-researched. Conventionally, urbanization has either improved or hindered carbon performance. However, this is not always the case as the paths of urbanization affecting carbon emission performance are diverse. Hence, this paper proposes a theoretical framework to investigate how urbanization influences carbon emission performance, specifically the indirect effects of land development/land-use efficiency, by taking the Yangtze River Delta urban agglomeration, China, as a study case. Empirical results show that urbanization improves carbon emission performance due to the agglomeration effect. As an intermediary pathway, land-use change has a two-sided impact on carbon emission performance. Urbanization can both worsen and improve carbon emission performance through increasing land-development intensity and promoting land-use efficiency, respectively. However, the positive impact of land-use efficiency can alleviate the problem of increasing carbon emissions caused by land over-development. Hence, the integration of urban planning strategies with land use management policies can help to achieve sustainable urbanization.